A multicomponent program improved cognitive and physical functions of older adults with lower GDS values - Ayuto Kodama; Miyuki Kodama; Mitsuyo Kato; Kaoru Sugawara; Hidetaka Ota (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2022)
Background: MCI is an intermediate stage between cognitive impairment status and persons with MCI are at high risk of developing AD. This study aimed to investigate the effects of a multicomponent program (aerobic, resistance exercises, cognitive training, music, myofascial release exercises, acupoint stimulation, and oral gymnastics) on the cognitive and physical functions of older adults in community dwellers and it is to clarify which measurement factors are predictive to reverse MCI to normal. Results: In this study, we measured cognitive functions, physical functions, and the diagnosis of MCI. We assessed factors before (pre-test), and after treatment of 12 training sessions (post-test). The participants were divided into two groups (Improve group and the Non-Improve group). The Mann-Whitney test was used to analyze the differences between pre-and post-test and revealed significant differences in the UWS (p < 0.05), WM (p < 0.01), SDST (p < 0.01), and MMSE (p < 0.01). Moreover, binomial logistic regression analysis revealed a significant association of the Improved group with the GDS-15 (Odds ratio, 0.587; 95% Confidence Interval [95% CI], 0.309-0.791; p = 0.003) and MMSE (Odds ratio, 0.494; 95 % CI, 0.360-0.957, p = 0.033).  Conclusion: This study indicated that this program improved physical and cognitive functions in those who were not prone to depression before treatment and suggests that the GDS measurement might be able to predict the intervention effects of a multicomponent program.